2023
DOI: 10.3390/agronomy13020491
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Babassu Industry By-Products as an Alternative Feed for Dairy Cows

Abstract: The objective of this study was to evaluate the fermentative characteristics, chemical composition, and in vitro digestibility of a total mixed ration silage containing two babassu by-products, starchy flour and babassu cake. The treatments were distributed in a completely randomised design containing four treatments and five replications. The treatments consisted of corn silage, corn silage based on the standard corn and soybean diet, corn silage with babassu flour, and corn silage with babassu cake. No signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…These results corroborate with studies by Zanine et al [36], who evaluated the fermentative characteristics and chemical composition of TMR containing flour and babassu cake with average results of DMR above 90%, confirming the low loss of DM when the inclusion of concentrates is considered in TMR silages.…”
Section: Discussionsupporting
confidence: 91%
“…These results corroborate with studies by Zanine et al [36], who evaluated the fermentative characteristics and chemical composition of TMR containing flour and babassu cake with average results of DMR above 90%, confirming the low loss of DM when the inclusion of concentrates is considered in TMR silages.…”
Section: Discussionsupporting
confidence: 91%
“…Bauer et al [18] examined the physical and chemical character istics of babassu oil for its potential use in the pharmaceutical and biofuel industries. Za nine et al [19] proposed a straightforward solution for feeding dairy cows by analyzin certain chemical properties. Moura et al [20] demonstrated the production of thermo plastic starch composites derived from starch and babassu fibers.…”
Section: Introductionmentioning
confidence: 99%
“…In this field, the BBM has the advantage of being available during the off‐seasons of conventional grains, making it an alternative for regional producers (Parente et al ., 2017) . This material has been investigated as a partial alternative energy source in ovine (Miotto et al ., 2012; Parente et al ., 2017; de Castro et al ., 2020) , caprine (Santos et al ., 2019, 2020), and bovine (da Cruz et al ., 2014; Ferreira et al ., 2022; Zanine et al ., 2023) diets. However, the use of BBM in ruminant diets may decrease digestibility and feed efficiency due to the increase in the indigestible fibre content, the reduced transit time of through the reticulorumen, and the heightened consumption of dry matter (Alencar et al ., 2015; Santana et al ., 2015).…”
Section: Babassu Coconutmentioning
confidence: 99%
“…From the fermentation point of view, babassu cake can be used as an alternative feed for ruminants, especially that require relatively high metabolisable protein levels (dos Santos‐Neta et al ., 2019). In the literature, this biomass had already been pointed as an alternative feed in ovine (de Sá et al ., 2015a), caprine (Oliveira et al ., 2021), dairy cattle (Ferreira et al ., 2022; Zanine et al ., 2023), and for lactating cows' diets, without depreciating their daily milk production (de Araújo et al ., 2021).…”
Section: Babassu Coconutmentioning
confidence: 99%